Optimal Risk Taking in an Uneven Tournament Game with Risk Averse Players - Matthias Kräkel (University of Bonn, Bonn Graduate School of Economics (BGSE), 2007)
We analyze the optimal choice of risk in a two-stage tournament game between two players that have different concave utility functions. At the first stage, both players simultaneously choose risk. At the second stage, both observe overall risk and simultaneously decide on effort or investment. The results show that those two effects which mainly determine risk taking - an effort effect and a likelihood effect - are strictly interrelated. This finding sharply contrasts with existing results on risk taking in tournament games with symmetric equilibrium efforts where such linkage can never arise. Hence, previous findings based on symmetry at the effort stage turn out to be nongeneric.
Keywords: M5; L1; C72; J3; 330; asymmetric equilibria; rank-order tournaments; risk taking; Risiko; Nichtkooperatives Spiel; Risikoaversion; Theorie